2016
DOI: 10.1111/jog.13151
|View full text |Cite
|
Sign up to set email alerts
|

17‐alpha‐hydroxyprogesterone caproate versus vaginal progesterone suppository for the prevention of preterm birth in women with a sonographically short cervix: A randomized controlled trial

Abstract: Our findings showed that vaginal progesterone and 17OHP-C had the same effect on the risk of preterm labor in asymptomatic women with a sonographically short cervix. We detected no significant difference between the effect of 17OHP-C and vaginal progesterone on CL changes over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…[44][45][46][47] One study compared cerclage (McDonald) with progesterone (IM 17-OHPC) 48 and six studies compared PV progesterone with IM 17-OHPC. [49][50][51][52][53][54] Only four studies included women with a previous preterm birth excluding those with a short cervix (defined as <15, <20, <25, and <28 mm), and three studies included women with a short cervix excluding those with a history of preterm birth (including one study with women with a cervical length of <30 mm). Twelve studies included women with a previous preterm birth, regardless of cervical length, and ten studies included women with a short cervix (usually defined as ≤25 mm, although one study included women with a cervical length of <30 mm), regardless of their preterm birth history.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…[44][45][46][47] One study compared cerclage (McDonald) with progesterone (IM 17-OHPC) 48 and six studies compared PV progesterone with IM 17-OHPC. [49][50][51][52][53][54] Only four studies included women with a previous preterm birth excluding those with a short cervix (defined as <15, <20, <25, and <28 mm), and three studies included women with a short cervix excluding those with a history of preterm birth (including one study with women with a cervical length of <30 mm). Twelve studies included women with a previous preterm birth, regardless of cervical length, and ten studies included women with a short cervix (usually defined as ≤25 mm, although one study included women with a cervical length of <30 mm), regardless of their preterm birth history.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The vaginal progesterone group had significantly lower rates of PTB <34 weeks of gestation, PTB at 28 to 32 weeks of gestation, and a lower rate of side effects. However, randomized trials comparing daily vaginal progesterone administration and weekly intramuscular injection of 250 mg of 17α-OHPC in singleton pregnant women with history of PTB or short CL did not show any significant differences in the rate of PTB <37 weeks of gestation, mean GAD, and neonate outcomes between the 2 groups [ 74 75 76 ]. A recent systematic review and meta-analysis showed that women who received vaginal progesterone had significantly lower rates of PTB <34 and <32 weeks of gestation, a lower rate of adverse drug reactions and a lower rate of NICU admission compared with women who received 17α-OHPC [ 77 ].…”
Section: Ohcp Intramuscular Injection Versus Vaginal Natural Micronmentioning
confidence: 99%
“…We identified five randomised controlled trials that compared vaginal progesterone and IM progestin for the prevention of PTB in singleton pregnant women with history of PTB or short CL (Table S5). 27–31 Daily gel (90 mg) was used for vaginal progesterone in one study, 27 and daily tablets (100‒400 mg) were used for vaginal progesterone in the other four studies 28–31 . The weekly administration of 250 mg 17‐OHPC was used for IM progestin in all studies.…”
Section: Resultsmentioning
confidence: 99%
“…We found that the efficacy of vaginal and IM progestogen therapies was equivalent in preventing PTB in women with a history of spontaneous PTB or short CL, however, consistent with previous studies (Table S5). 28–31 …”
Section: Discussionmentioning
confidence: 99%